Comparing fall migration of three Catharus species using a radio-telemetry network - Marchand Camille Bégin (De Gruyter, 2020)
Migration routes vary greatly among small passerine species and populations. It is now possible to determine the routes over great distances and long periods of time with emerging monitoring networks. We tracked individual Swainson’s Thrush (Catharus ustulatus), Bicknell’s Thrush (Catharus bicknelli) and Gray-cheeked Thrush (Catharus minimus) in northeastern Quebec and compared their migration routes and paces across an array of radio-telelemetry stations in North America. Swainson’s Thrush migrated further inland than the other two species. Individuals from all three species slowed their migration pace in the southeastern United States, and Swainson’s Thrush was more likely to stopover than Bicknell’s Thrush. Although individuals were tagged in a small area within or close to their breeding range, the results document the variability of migration routes between species with similar ecological characteristics and provide detailed material to be used for migration studies with broader taxonomic or ecological scope.